Analysing the Listing Process on Main Market and Alternative Investment Market of London Stock Exchange for Indian Companies - Unadkat, Neerav (2011)
This Management Project analyses the listing process for Indian Companies on the Main Market (MM) and Alternative Investment Market (AIM) of the London Stock Exchange.